Checklist of water mites from the Balkan Peninsula: second supplement, new DNA barcodes and description of a new species - Pešić, Vladimir; Bankowska, Aleksandra; Goldschmidt, Tom; Hårsaker, Karstein; Jovanović, Milica; Kaitetzidou, Elisavet; Krakowiak, Maja; Kozłowska, Aleksandra; Michaloudi, Evangelia; Michoński, Grzegorz; Miliša, Marko; Pozojević, Ivana; et al. (Zootaxa, 2025)
Knowledge of the water mite fauna in the Balkans is still very heterogeneous and far from complete. A compilation of published data is considered the first step in creating an up-to-date comprehensive checklist of water mites of the Balkans. In this supplement, we list all species reported from the Balkans from November 2017 to date and provide an updated checklist of water mites that inhabit the Balkan countries. With the additions in this study, the number of water mite species inhabiting the Balkan Peninsula has increased to 426 species and subspecies. One species, Sperchon balcanicus Pešić, sp. nov. (Sperchontidae), is described as new to science. This study adds 299 new barcodes to the existing DNA barcode reference library that now includes 1032 COI DNA barcodes from the Balkans publicly available through the Barcode of Life Data Systems (BOLD). Still, only one-third of the currently known species of water mites in the Balkans now have reference barcodes in BOLD, indicating the need for future integrative research on the morphological and genetic diversity of Balkan water mites.